Determinan Cash Holdings Perusahaan: Studi Pada Perusahaan Manufaktur di Indonesia - Setiawan, Rahmat; Rachmansyah, Adyanto Budi (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
There is an increased in firm’s awareness of the importance of firm’s liquidity level to avoid financial distress after global crisis in 2008. Liquidity is the company's ability in paying their liabilities due using their liquid asset that owned by firms such as cash and cash equivalent Aim of this study is to test empirically the determinants of corporate cash holdings in Indonesia. A sample of 97 Indonesian manufacturing firms listed on Indonesia Stock Exchange (IDX) for a period of 6 years (from 2011-2016) was selected. This study used ordinary least square regression research design. The results of this study show that firm size, profitability, dividend payment, capital expenditure, and cash flow have a significant effect to the corporate cash holdings of Indonesian manufacturing firms. This study gives contribution to the literature on the firm characteristic variables that determine the corporate cash holdings on Indonesian manufacturing firms. The results may be useful for decision-making for the financial managers, financial management consultants, and investors.Keywords: Leverage, Firm Size, Profitability, Capital Expenditure, Dividend Payment, Cash Flow, Cash Holding